THE EFFECT OF HERBAL EXTRACTS AND PROBIOTIC FEEDING ON PRODUCTIVITY AND QUALITY OF BROILERS - Hasibuan, Ahmad Syukur; Silalahi, J; Masfria, M (Asian Journal of Pharmaceutical Research and Development, 2019)
ABSTRACT Objective: To find out the effect of probiotics, javanese turmeric (Curcuma xanthorrhiza) and breadfruit (Artocarpus altilis) leaves extract in feedon productivity and quality of broilers. Design: The design of this study was experimental research. The viscous herbal extract from javanese turmeric and breadfruit leaves were prepared by maceration with 96% ethanol and the probiotics used EM4 (Effective Microorganisms-4). This study used male chicks and divided into 5 groups: (1) negative control treatment (feed), (2) positive controls (feed+antibiotics), (3) feed+0.1% extract+1% probiotics, (4) feed+0.2% extract+2% probiotics and (5) feed +0.3% extract+3% probiotics. The positive control used erythromycin. Feed intake, body weight gain and feed conversion rate were observed for 35 days. Total cholesterol and crude protein levels were examined on day 35. Interventions: The intervened variable was the concentration of extract used. Main outcome measures: The main measurement in this study were feed conversion rate,total cholesterol and crude protein levels. Results: The results showedthat combination of probiotics, javanese turmeric and breadfruit leaves herbal extract increased body weight 10.71% and feed intake 61.60%, decreased feed conversion 13.97% and total cholesterol 27.95% of treatment group and significantly different with negative and positive control groups (p<0.05) but did not affect (p>0.05) to crude protein levelsof treatment group or negative and positive control group. Conclusion: The administration of probiotics, javanese turmeric and breadfruit leaves herbal extract increased productivity and decreased cholesterol levels but did not affect crude protein levels in broilers.